Pendugaan Kesehatan Pohon di Kebun Raya Bogor, Jawa Barat: Trees Health Assessment in Bogor Botanical Garden, West Java - Safira Nabawiah; Erianto Indra Putra; Elis Nina Herliyana; Arief Noor Rachmadiyanto (PERENNIAL, 2025)
Bogor Botanical Garden (BBG) is an ex-situ plant conservation area intended for conservation, research, education, tourism, and environmental services. As a tourist destination, BBG attracts many people every day. Human activities and unfavourable environmental conditions have caused damage to the existing collection. In 2021, 2022, and 2023, tree health monitoring was carried out using the Forest Health Monitoring method and repeated in 2024 by this research to assist the BBG management in ensuring the tree collections remain healthy and sustainable and provide a safe and comfortable environment for visitors. Seven clusters based on tree family dominance have been made for tree health monitoring. The monitoring includes the location, type, and severity of damage to individual trees in clusters 2, 3, 5, and 6. Some new damage types are found in the clusters. However, Damage Index values (DIV) in 2024 at clusters 2, 3, and 6 are categorized as healthy and DIV cluster 5 has changed to the light damage category. We observed that damages that have occurred are interdependent, where one damage can cause another damage. These findings suggest the importance of the BBG managers to provide immediate action on damaged trees to maintain the collections.